13/#381 The role of postoperative radiation after radical hysterectomy for women with early-stage neuroendocrine carcinoma of the cervix: a meta-analysis. (4th December 2022) - Kim, Catherine; Salvo, Gloria; Ishikawa, Mitsuya; Chen, Tze-Chien; Frumovitz, Michael
Abstract : Objectives: Neuroendocrine carcinoma of the cervix (NECC) is an aggressive disease with high rates of nodal disease spread even in seemingly cervix-confined disease. Therefore, many providers prescribe postoperative radiation therapy in an effort to reduce recurrences. However, large studies evaluating the utility of this approach are lacking. The objective of this study was to determine recurrence and mortality in patients with early-stage NECC who had pelvic radiation after radical hysterectomy compared to those who did not receive radiation. Methods: We performed a meta-analysis of 13 unique studies that reported recurrence and/or mortality for patients with early-stage NECC who underwent radical hysterectomy with or without adjuvant radiation therapy. Results: In 6 studies that reported overall recurrence rates, 65 (51.6%) of 126 patients who received postoperative radiation recurred compared to 71 (37.0%) of 192 patients who did not (RR 1.25, 95% CI: 0.93–1.66, p=0.14). In 6 studies that reported pelvic recurrence rates, there were 15 pelvic recurrences (11.9%) in the 126 patients who received postoperative radiation compared to 46 pelvic recurrences (24.0%) in the 192 patients who did not (RR 0.59, 95% CI: 0.33 – 1.05, p= 0.07). In 12 studies that reported mortality rate, there were 129 deaths (33.1%) in 390 patients who received postoperative radiation therapy compared to 207 (35.1%) in 589 patients who did not (RR 1.00, 95% CI: 0.74–1.36, p=0.99). Conclusions: The addition of postoperative radiation therapy after radical hysterectomy may reduce pelvic recurrences but does not appear to decrease overall recurrence or death in women with early-stage NECC.